Large-Scale “OMICS” Studies to Explore the Physiopatholgy of HIV-1 Infection - Le Clerc, Sigrid; Limou, Sophie; Zagury, Jean-François (Frontiers in Genetics, 2019)
In this review, we present the main large-scale experimental studies that have been performed in the HIV/AIDS field. These ‘omics’ studies are based on several technologies including genotyping, RNA interference, transcriptome or epigenome analysis. Due to the direct connection with disease evolution, there has been a large focus on genotyping cohorts of well-characterized patients through genome-wide association studies (GWAS), but there have also been several in vitro studies targeting siRNA interference of HIV-1 infected cells or transcriptome analyses. After describing the major results obtained with these omics technologies -including some with a high relevance for HIV-1 treatment-, we discuss the next steps that the community needs to embrace in order to derive new actionable therapeutic or diagnostic targets. Only integrative approaches that combine all big data results and consider their complex interactions will allow to capture the global picture of HIV molecular pathogenesis. This novel challenge will require large collaborative efforts and represents a huge open field for innovative bioinformatics approaches.